RNA repair: an antidote to cytotoxic eukaryal RNA damage - Nandakumar, Jayakrishnan (2008)
RNA healing and sealing enzymes drive informational and stress response pathways entailing repair of programmed 2’,3’ cyclic PO(4)/5’-OH breaks. Fungal, plant and phage tRNA ligases use different strategies to discriminate the purposefully broken ends of the anticodon loop. Whereas phage ligase recognizes the tRNA fold, yeast and plant ligases do not and are instead hard-wired to seal only the tRNA 3’-OH, 2’-PO(4) ends formed by healing of a cyclic phosphate. tRNA anticodon damage inflicted by secreted ribotoxins such as fungal γ-toxin underlies a rudimentary innate immune system. Yeast cells are susceptible to γ-toxin because the sealing domain of yeast tRNA ligase is unable to rectify a break at the modified wobble base of tRNA(Glu(UUC)). Plant and phage tRNA repair enzymes protect yeast from γ-toxin because they are able to reverse the damage. Our studies underscore how a ribotoxin exploits an Achilles’ heel in the target cell’s tRNA repair system.